Risk and resiliency: psychosocial and behavioral determinants of drunkenness, tobacco, and cannabis use among adolescents in the northern Mediterranean region - Maor, Rotem; Giladi, Ariela; Ben-Meir, Lilach; Walsh, Sophie D.; Tesler, Riki; Ivanoska, Kalina Sotiroska; Harel-Fisch, Yossi (Springer Science and Business Media LLC, 2023)
Adolescence is a critical period of growth in which youth are vulnerable to a variety of risk factors that affect their development, including exposure to psychoactive substances. Studies showed that health risk behaviors tend to be interrelated with evidence suggesting a cumulative impact of these behaviors. The current study aims to examine the accumulation of risk factors and the accumulated lack of resiliency factors that predict substance use among youth in the northern Mediterranean region. Data were obtained from the Health Behavior in School-Aged Children study in 2018/2019. Adolescents (10,084; age 15; 51.7% girls) were selected using representative cluster sampling and surveyed by questionnaire in the classroom. Findings revealed that cumulative risk factors and a cumulative lack of resiliency factors were associated with a higher likelihood of psychoactive substance use. Furthermore, each additional unit of increase in either risk factors or lack of resiliency factors demonstrated higher odds of substance use. Among the examined resiliency factors, negative school feelings and lack of familial support emerged as the most significant predictors of substance use. Likewise, early sexual initiation was the most prominent predictor among the examined risk factors. Our findings demonstrated the importance of resiliency factors in reducing adolescents’ risk behaviors. It may also contribute to developing and implementing intervention programs specifically designed for the shared characteristics and culture of the Mediterranean countries to prevent substance use among adolescents.